Prognostic performance of early immune and endothelial activation markers in mild-to-moderate COVID-19 outpatients: a nested case-control study - Alemany, Andrea; Balanza, Núria; Millat-Martinez, Pere; Ouchi, Dan; Corbacho-Monné, Marc; Morales-Indiano, Cristian; Fernández Rivas, Gema; Blanco, Ignacio; Mitjà, Oriol; Aguilar, Ruth; Dobaño, Carlota; Bassat, Quique; et al. (Frontiers in Immunology, 2024)
IntroductionEvidence on the association of biomarkers of host response to infection with COVID-19 clinical outcomes has focused mainly on hospitalized patients. We investigated the prognostic performance of 39 immune and endothelial activation markers measured early in the course of disease to predict the development of severe COVID-19 and hospitalization.MethodsWe conducted a nested case-control study from a randomized clinical trial evaluating the efficacy of COVID-19 convalescent plasma in outpatients aged 50 years or older presenting with mild-to-moderate COVID-19. We selected participants who were hospitalized within 28 days (cases) and who were not (controls) to compare their biomarker levels in plasma samples collected at enrolment.ResultsA total of 42 cases and 42 controls were included in this study. The levels of CRP, IL6, IP10, ferritin, IFNα, IL8, IL1RA, MCP1, and RANTES, determined within 7 days of symptoms onset, showed good individual prognostic performance for COVID-19 associated hospitalization by day 28. The biomarkers CRP, IL6, IP10, IL8, IL1RA, and suPAR showed good individual prognostic performance for severe COVID-19. CRP, IL6 and IP10 had the most robust association with both hospitalization and severe COVID-19, with CRP having the highest discriminatory capacity with hospitalization, and IL6 for severe COVID-19.DiscussionOur study shows good prognostic performance of CRP and IL6 for 28-day hospitalization in patients with mild-to-moderate COVID-19, in the absence of clinical criteria for admission upon enrolment. These findings confirm the value of these biomarkers at early stages of COVID-19 disease in the outpatient setting to support management decisions.